The extent to which Egyptian elites communicate with interact with the activities of public relation in non-government international organizations - Al-Sabri, Ahmed Mustafa Kamel (Arab Journal for Sciences and Research Publishing, 2017)
The goal of the research is to discover the extent of the Egyptian Elites communicate with the activities of public relation in nongovernment international organizations by considering these international organizations aimed to achieve development in local communities will not succeed in achieving its performance except with the participation all sectors of local communities and it come in top of those sectors elites and opinion leaders. The main question of the research was what is the extent of the Egyptian Elites communicated with the activities of public relation for the international nongovernment organizations? This research belongs to the discovering research and the researcher implemented his study on different groups of professional Elites, and the research reached to many results the most important is increased the rate of Elites interest in the work fields of those organizations, and reduction in rate of those who didn’t communicate directly with those organizations.